CONSUMER’S CIVILIZATION: THE SCOPE OF GROWTH - Оноприенко, В. И. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
A consumer’s civilization that has arisen in the world causes a great uneasiness among philosophers, sociologists, psychologists and others. Some factors and possible reasons, which promote its progress, are researched in the article.